Assessment for Inclusion in Higher Education Promoting Equity and Social Justice in Assessment - Ajjawi, Rola; Tai, Joanna; Boud, David; Jorre de St Jorre, Trina (Taylor & Francis, 2023)
Bringing together international authors to examine how diversity and inclusion impact assessment in higher education, this book provides educators with the knowledge and understanding required to transform practices so that they are more equitable and inclusive of diverse learners. Assessment drives learning and determines who succeeds. Assessment for Inclusion in Higher Education is written to ensure that no student is unfairly or unnecessarily disadvantaged by the design or delivery of assessment. The chapters are structured according to three themes: 1) macro contexts of assessment for inclusion: societal and cultural perspectives; 2) meso contexts of assessment for inclusion: institutional and community perspectives; and 3) micro contexts of assessment for inclusion: educators, students and interpersonal perspectives. These three levels are used to identify new ways of mobilising the sector towards assessment for inclusion in a systematic and scholarly way. This book is essential reading for those in higher education who design and deliver assessment, as well as researchers and postgraduate students exploring assessment, equity and inclusive pedagogy.